Neuraxial labor analgesia: is there a place for neuraxial adjuvants beyond opioids. Issue 1 (May 2022) - Cavens, Loore; Roofthooft, Eva
Abstract : Neuraxial labor analgesia is considered the gold standard technique for analgesia. Ideally, a good neuraxial technique uses dilute local anesthetic solutions to produce effective pain relief with no or minimal motor impairment. Adjuvant drugs that are co-administered with the local anesthetic either epidurally or intrathecally are useful in achieving this goal. The current review focuses on the effectivity and side–effect profile of various commonly used or tested adjuvants.